Mgm101p Is a Novel Component of the Mitochondrial Nucleoid That Binds DNA and Is Required for the Repair of Oxidatively Damaged Mitochondrial DNA - Meeusen, Shelly (The Rockefeller University Press, 1999)
Maintenance of mitochondrial DNA (mtDNA) during cell division is required for progeny to be respiratory competent. Maintenance involves the replication, repair, assembly, segregation, and partitioning of the mitochondrial nucleoid. MGM101 has been identified as a gene essential for mtDNA maintenance in S. cerevisiae, but its role is unknown. Using liquid chromatography coupled with tandem mass spectrometry, we identified Mgm101p as a component of highly enriched nucleoids, suggesting that it plays a nucleoid-specific role in maintenance. Subcellular fractionation, indirect immunofluorescence and GFP tagging show that Mgm101p is exclusively associated with the mitochondrial nucleoid structure in cells. Furthermore, DNA affinity chromatography of nucleoid extracts indicates that Mgm101p binds to DNA, suggesting that its nucleoid localization is in part due to this activity. Phenotypic analysis of cells containing a temperature sensitive mgm101 allele suggests that Mgm101p is not involved in mtDNA packaging, segregation, partitioning or required for ongoing mtDNA replication. We examined Mgm101p's role in mtDNA repair. As compared with wild-type cells, mgm101 cells were more sensitive to mtDNA damage induced by UV irradiation and were hypersensitive to mtDNA damage induced by gamma rays and H(2)O(2) treatment. Thus, we propose that Mgm101p performs an essential function in the repair of oxidatively damaged mtDNA that is required for the maintenance of the mitochondrial genome.